2013
DOI: 10.1111/1471-0528.12173
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared fluorescence sentinel lymph node biopsy in vulvar cancer: a randomised comparison of lymphatic tracers

Abstract: This study aims to confirm feasibility of near-infrared (NIR) fluorescence imaging for sentinel lymph node (SLN) biopsy in vulvar cancer and to compare the tracer indocyanine green (ICG) bound to human serum albumin (HSA) versus ICG alone. Patients received 99mTc-nanocolloid and patent blue for SLN detection. Subsequently, patients randomly received ICG:HSA or ICG alone. In 24 patients, 35 SLNs were intraoperatively detected. All SLNs detected were radioactive and NIR fluorescent and 27 (77%) were blue. No sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…However, all these data may be organ-dependent, so it is presently unknown if this is also the case in ovarian cancer. Moreover, newly developed hybrid SN detection agents, combining radioactivity with fluorescence or paramagnetic capabilities; alternative operative techniques such as multiphased injection; and new intraoperative imaging technologies may provide additional advantages (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…However, all these data may be organ-dependent, so it is presently unknown if this is also the case in ovarian cancer. Moreover, newly developed hybrid SN detection agents, combining radioactivity with fluorescence or paramagnetic capabilities; alternative operative techniques such as multiphased injection; and new intraoperative imaging technologies may provide additional advantages (24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…166 In 32 women with vulvar cancer, 35 SLNs in 24 patients were intraoperatively detected by NIRF imaging using ICG:HSA and ICG alone, though no significant difference was found between them. 167 In Rossi et al's study, 17 out of 20 patients with cervical or endometrial carcinoma were observed with SLNs by ICG injection in the cervix, demonstrating that it is a reliable method for intraoperative SLNs mapping. 168 Eighteen patients with confirmed neoplasia underwent NIR laparoscopy that could transmit both white light and NIR image.…”
mentioning
confidence: 95%
“…79 Schaafsma et al compared ICG conjugated with albumin (ICG:HSA) with ICG in 24 vulvar cancer patients; HSA was expected to enhance detection because of increased lymphatic uptake. [80][81][82] All 35 nodes were identified in both groups and ICG:HSA did not appear to confer an advantage over ICG alone.…”
Section: Genitourinary Cancersmentioning
confidence: 90%